2020
DOI: 10.3389/fmicb.2020.595023
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Laboratory Evolution of Native Torulaspora delbrueckii YCPUC10 With Enhanced Ethanol Resistance and Evaluation in Co-inoculated Fermentation

Abstract: Torulaspora delbrueckii is a yeast species typically present in the early stages of the fermentation process. T. delbrueckii positively modifies the aromatic properties of wines. However, its contribution to the final quality of the wine is restricted by its low tolerance to ethanol. T. delbrueckii is capable of fermenting and tolerating an ethanol concentration ranging from 7.4% (v/v) to slightly higher than 9% (v/v). For this reason, it cannot complete fermentation, when alcohol reach levels higher than 12% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Although non-Saccharomyces yeasts have low tolerance to ethanol, our results show that some can be isolated once the alcoholic fermentation was completed (Table 2). Catrileo, Acuña-Fontecilla, and Godoy (2020) reported that T. delbrueckii YCPUC10, isolated from C. Sauvignon grape juice, was able to persist with ethanol levels of about 11% as the result of an adaptative metabolism [79]. Furthermore, certain non-Saccharomyces are able to increase their ethanol tolerance by producing succinic acid [80] and this might be the case of the Metschnikowia, Torulospora, Hanseniospora, and Candida spp.…”
Section: Sauvignon Blancmentioning
confidence: 99%
“…Although non-Saccharomyces yeasts have low tolerance to ethanol, our results show that some can be isolated once the alcoholic fermentation was completed (Table 2). Catrileo, Acuña-Fontecilla, and Godoy (2020) reported that T. delbrueckii YCPUC10, isolated from C. Sauvignon grape juice, was able to persist with ethanol levels of about 11% as the result of an adaptative metabolism [79]. Furthermore, certain non-Saccharomyces are able to increase their ethanol tolerance by producing succinic acid [80] and this might be the case of the Metschnikowia, Torulospora, Hanseniospora, and Candida spp.…”
Section: Sauvignon Blancmentioning
confidence: 99%
“…The T. delbrueckii species is usually defined as a low ethanol producer [ 2 , 25 , 76 ], however in the work of Escribano et al [ 33 ], T. delbrueckii was also one of the highest ethanol producers, among the non- Saccharomyces species tested. Additionally, Canonico et al [ 77 ] reported ethanol production in values higher than 12% ( v / v ) by T. delbrueckii strains, and Catrileo et al [ 78 ], using adaptive laboratory evolution, were able to obtain a strain capable of producing ethanol levels of 11.5% ( v / v ). In this way, we concluded that this characteristic is strain-dependent, and should not be attributed as a feature associated to the species.…”
Section: Resultsmentioning
confidence: 99%
“…When considering K. marxianus, strains with higher growth rates were obtained under stressful high ethanol environments [116], within the range of 7-10% (v/v) of ethanol [117]. In a similar way, a recent study and, to the extent of our knowledge, the only report applying this technique to the generation of T. delbrueckii evolved strains, was conducted by Catrielo et al [96]. The authors efficiently obtained evolved clones of T. delbrueckii with improved growth kinetic parameters, increased ethanol resistance, variants capable of tolerating ethanol concentrations of 11.5% (v/v), and additional higher resistance to SO 2 , in comparison with the original strain.…”
Section: Genetic Tools Employed Towards T Delbrueckii Improvementmentioning
confidence: 90%
“…In recent years, CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/associated protein 9) revolutionized research as a gene-based editing mechanism allowing the selective manipulation of DNA [92,93]. Although there is yet no current employment of CRISPR towards T. delbrueckii, this engineering tool has been extensively used for other non-conventional yeasts such as Yarrowia lipolytica, Pichia pastoris, Komagataella phaffii, Kluyveromyces lactis, Kluyveromyces marxianus [94], Schizosaccharomyces pombe, Candida albicans and Candida glabrata, and for the conventional yeast S. cerevisiae [92][93][94][95][96][97].…”
Section: Genetic Tools Employed Towards T Delbrueckii Improvementmentioning
confidence: 99%
See 1 more Smart Citation